Study on inflection and shear stress and calculation of reinforced concrete beams affected by these stresses - Manrique, Hector (Revista Universidad de Guayaquil, 1934)
688 / 5.000 Resultados de traducción Resultado de traducción Bending is the effect produced in any piece or beam when, under the action of forces in opposite directions acting at different points on it, it bends in a certain way. When the line of action of the forces is normal to the plane of the piece on which they fall, the bending is called simple; when it is oblique, it is called compound. In the present study we will only consider the first. Suppose a piece or beam is supported at its two ends. If we consider that a force P has been applied to it at any point of its span, acting downwards, the piece will bend and adopt a shape similar to that drawn in the dotted line.